👤

what is the constant term of f(x)= x⁴-5x²+4?​

Sagot :

y=4

Step-by-step explanation:

f(x)=x⁴-5x²+4

y=x⁴-5x²+4

0=x⁴-5x²+4

1. Ask: Which two numbers add up to−5 andmultiply to 4?

−4 and -1

2. Rewrite the expression using the above.

•(x^2 −4)(x^2 −1)

•0=(x^2-4)(x^2-1)

3.Rewrite x^2 −4 in the form a^2-b^2 where a=x and b=2.

•0=(x^2 −2^2 )(x^2 −1)

4.Use Difference of Squares:a^2 −b^2 =(a+b)(a−b).

•0=(x+2)(x−2)(x^2 −1)

5.Rewrite x^2 −1 in the form a^2- b^2, where a= x and b= 1.

•0=(x+2)(x−2)(x^2 - 1^2 )

6 Use Difference of Squares:a^2 −b^2 =(a+b)(a−b).

•0=(x+2)(x−2)(x+1)(x−1)

7 Switch sides.

•(x+2)(x−2)(x+1)(x−1)=0

8.Solve for x.

1 Ask: When will (x+2)(x−2)(x+1)(x−1) equal zero?

•When x+2=0, x−2=0, x+1=0, or x−1=0

2 Solve each of the 4 equations above.

•x=±2,±1

2. y-Intercept

1 Let x=0 to find the y-intercept(s).

•y=0^4 −5×0^2+4

> y=0^4-5×0^2+4

1.x-Intercept

1.Let y=0 to find the x-intercept(s).

•0=0^4-5×0^2+4

2.Simplify 0^4 to 0.

•0=0-5 0^2+4

3.Simplify 0^2 2 to 0.

•0=0−5×0+4

4.Simplify 5×0 to 0.

•0=0-0+4

5.Simplify 0-0 to 0.

•0=0+4

6.Simplify 0+4 to 4.

•0=4

2. y-Intercept

1.Let x=0x=0 to find the y-intercept(s).

y=0^4−5×0^2+4

2.Simplify.

y=4